The Austronesians : historical and comparative perspectives - Bellwood, Peter S.; Fox, James J., 1940-; Tryon, D. T. (Darrell T.) (Occasional paper of the Department of Anthropology, Research School of Pacific Studies, the Australian National University., 2006)
The Austronesian-speaking population of the world are estimated to number more than 270 million people, living in a broad swathe around half the globe, from Madagascar to Easter Island and from Taiwan to New Zealand. The seventeen papers in this volume provide a general survey of these diverse populations focusing on their common origins and historical transformations. The papers examine current ideas on the linguistics, prehistory, anthropology and recorded history of the Austronesians.